Portrait of Arnold O. Beckman (1900-2004)
Dr. Arnold O. Beckman (1900-2004), pictured here with a DU Spectrophotometer, invented the first commercially successful electric pH meter in 1934. Thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation.
Keywords: Scientists--Portraits; Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.; Beckman, Arnold O.